Cephalopods, as a Source of New Antimicrobial Substances - N. N. Besednova; N. N. Kovalev; T. S. Zaporozhets; T. A. Kuznetsova; A. K. Gazha (Антибиотики и Химиотерапия, 2020)
Under the conditions of emergence of microbial strains with new properties, including antibiotic resistance, in human and animal populations the search for new antimicrobial substances with improved pharmacological properties and new mechanisms of action from natural objects, in particular from aquatic organisms, is continued. This review presents extensive data on antibacterial, antiviral and antifungal properties of biologically active substances (BAS) of different chemical nature, recovered from representatives of the class of cephalopods (squid, octopus, cuttlefish, nautilus). Analysis of the literature shows that antibacterial activity of some BAS is not inferior, but in some cases is even superior to that of the available antibiotics. The authors note that the review includes the results, mainly of the in vitro studies. Adequate extrapolation of these data to the in vivo conditions is required, that could serve as foundation for development of new generations of medicinal compounds, functional foods and biologically active food supplements.